Implementasi Peraturan Walikota Padang Nomor 38 Tahun 2021 tentang Pengelolaan Kampung Nelayan - Aldo Ramayanto; Kusdarini Kusdarini; Muhammad Ichsan Kabullah (Journal of Social and Policy Issues, 2023)
This research is motivated by the existence of the Padang City Government policy on the management of fishing villages, which aims to optimize the arrangement of fishing villages, improve the fishermen's welfare, increase the effectiveness and efficiency of fishing village areas, and realize coordination, integrity, synchronization, and consistency between related parties in the management of fishing villages. If you look at the condition of fishermen in Padang City, especially in Pasie Nan Tigo Village, it is a step to carry out this policy so that the fishing community in this village can improve their welfare with the existence of this fishing village. The research was conducted using a descriptive type of qualitative method. Data was gathered through interviews with the chosen informants through a purposive sampling technique, supplemented by observation and documentation studies, and analyzed using Miles and Huberman's data analysis techniques. This study uses the theory of implementation according to Donald S. Van Meter and Carl E. Van Horn, which consists of six variables, namely policy standards and objectives, resources, inter-organizational communication and strengthening of implementing activities, characteristics of implementing agents, disposition of implementors, and the economic, social, and political environment. The results of this study show that the implementation of the Padang Mayor Regulation Number 38 of 2021 concerning the Management of Fishermen's Villages has been running but is not optimal yet. This can be seen in the budgetary resources that were been constrained during the COVID-19 pandemic and the inflation in the city of Padang. As well as the influence of the social, economic, and political environment on the implementation of policies. Therefore, the Padang City Fisheries and Food Service, as the leading sector, needs to maximize all resources and improve coordination and communication so that this policy can run optimally.